The SP1/SIRT1/ACLY signaling axis mediates fatty acid oxidation in renal ischemia–reperfusion-induced renal fibrosis - Wu, Huailiang; Wang, Liyan; Kang, Peng; Zhou, Xiangjun; Li, Wei; Xia, Zhongyuan (International immunopharmacology, 2024)
•The expression of Sirt1 was decreased in renal fibrosis induced by renal ischemia–reperfusion.•Overexpression or knockout Sirt1 in vivo alleviated and aggravated renal fibrosis.•Sirt1 regulated the ACLY transcription by inhibited the enrich of H3K27ac in the promoter of ACLY.•Fatty acid oxidation mediated by ACLY was inhibited in renal fibrosis induced by renal ischemia–reperfusion. Renal ischemia–reperfusion is the primary cause of acute kidney injury (AKI). Clinically, most patients who experience ischemia–reperfusion injury eventually progress gradually to renal fibrosis and chronic kidney disease (CKD). However, the underlying mechanism for AKI to CKD transition remain absent. Our study demonstrated that the downregulation of sirtuin 1 (Sirt1)-mediated fatty acid oxidation (FAO) facilitates IRI-induced renal fibrosis. The IRI animal model was established, and ribonucleic acid (RNA) sequencing was used to explore potential differentially expressed genes (DEGs) and pathways. The SIRT1 knockout mice were generated, and a recombinant adeno-associated virus that overexpresses SIRT1 was injected into mice to explore the function of SIRT1 in renal fibrosis induced by renal IRI. In vitro, hypoxia/reoxygenation (H/R) was used to establish the classical model of renal IRI and overexpression or knockdown of SIRT1 to investigate the SIRT1 function through lentiviral plasmids. The underlying molecular mechanism was explored through RNA sequencing, bioinformatics analysis, and chromatin immunoprecipitation assay. RNA sequencing analysis and western blot demonstrated that the expression of SIRT1 was significantly decreased in IRI mice. Overexpression of SIRT1 improved renal function and reduced lipid deposition and renal fibrosis. On the contrary, knockout of SIRT1 aggravated kidney injury and renal fibrosis. RNA sequencing, bioinformatics analysis, and chromatin immunoprecipitation assay mechanistically revealed that SIRT1 impairs the acetylation of histone H3K27 on the promoter region of ACLY, thereby impeding FAO activity and promoting renal fibrosis. Additionally, SP1 regulated FAO by directly modulating SIRT1 expression. Our findings highlight that downregulation of SIRT1-modulated FAO facilitated by the SP1/SIRT1/ACLY axis in the kidney increases IRI, suggesting SIRT1 to be a potential therapeutic target for renal fibrosis induced by renal IRI.